Auxiliary Partial Orthotopic Liver Transplantation for Selected Noncirrhotic Metabolic Liver Disease. Issue 1 (4th January 2019) - Rammohan, Ashwin; Reddy, Mettu S.; Narasimhan, Gomathy; Rajalingam, Rajesh; Kaliamoorthy, Ilankumaran; Shanmugam, Naresh; Rela, Mohamed
Abstract : Auxiliary partial orthotopic liver transplantation (APOLT) in selected noncirrhotic metabolic liver diseases (NCMLDs) is a viable alternative to orthotopic liver transplantation (OLT) as it supplements the function of the native liver with the missing functional protein. APOLT for NCMLD is not universally accepted due to concerns of increased technical complications and longterm graft atrophy. Review of a prospectively collected database of all pediatric patients (age ≤16 years) who underwent liver transplantation for NCMLD from August 2009 up to June 2017 was performed. Patients were divided into 2 groups: group 1 underwent APOLT and group 2 underwent OLT. In total, 18 OLTs and 12 APOLTs were performed for NCMLDs during the study period. There was no significant difference in the age and weight of the recipients in both groups. All APOLT patients needed intraoperative portal flow modulation. Intraoperative peak and end of surgery lactate were significantly higher in the OLT group, and cold ischemia time was longer in the APOLT group. There were no differences in postoperative liver function tests apart from higher peak international normalized ratio in the OLT group. The incidence of postoperative complications, duration of hospital stay, and 1‐ and 5‐year survivals were similar in both groups. In conclusion, we present the largest series of APOLT for NCMLD. APOLT is a safe and effective alternative to OLT and may even be better than OLT due to lesser physiological stress and the smoother postoperative period for selected patients with NCMLD.